Orbital and adnexal sarcoidosis: Clinical presentations and management outcomes - Shebin Salim; Md Shahid Alam; Sonam Ahuja; Kirthi Koka; Marian Pauly; Subramanian Krishnakumar; Bipasha Mukherjee (Indian Journal of Ophthalmology)
Purpose: To present the clinical features and management outcomes in a series of patients with orbital and adnexal sarcoidosis. Methods: This was a retrospective analysis of 19 histopathologically proven cases of orbital and adnexal sarcoidosis over the past ten years. The data analyzed included demographic details, clinical and imaging features, and management outcomes. The response to treatment was categorized based on clinical improvement at the last follow-up as complete resolution, partial resolution, or no resolution. Results: There were 15 (78.9%) females and four (21%) males. The mean age at presentation was 51.05 ± 14.35 years. Upper lid swelling was the most common sign (n = 6), followed by lacrimal gland enlargement (n = 5). The specific locations of involvement were orbital soft tissues (n = 8), lid (n = 5), lacrimal gland alone (n = 3), lacrimal sac (n = 1), extra ocular muscles (n = 1), and conjunctiva (n = 1). An incisional biopsy was performed on 16 patients, and an excisional biopsy on three. Of those undergoing excisional biopsy, the lesion was located in the superonasal extraconal space in one and in the superotemporal lid in two. Twelve patients (63.2%) had systemic involvement at presentation. No further treatment was necessary for patients who underwent excisional biopsy. Additional treatments included oral steroids (n = 10) and systemic immunosuppressants (n = 5). Six patients were lost to follow-up. Complete resolution of signs and symptoms was noted in 11 patients (84.6%), while partial resolution was seen in two patients. The mean duration of follow-up was 7.56 ± 12.63 months. Conclusion: Sarcoidosis can affect any part of the orbit or adnexa, with varied presentations depending on the involvement. Excisional or incisional biopsies, along with systemic steroids and immunosuppressants in select cases, remain the mainstay of treatment.